Immunological aspects of glycosylation: from aberrant to defective glycosylation - Pascoal, Carlota Moutinho (2018)
Glycosylation is crucial in many biological processes, like cell recognition, signaling and development. Many diseases present altered glycosylation and two extremes are cancer and congenital disorders of glycosylation (CDG), with aberrant and defective glycosylation, respectively. Sialic acids are glycans’ terminal sugars with an immunomodulatory role and when decreased, typically activate immune cells, as dendritic cells. Interestingly, both ST6Gal-I and its derived α2,6 sialylation are overexpressed in cancer. Here, we hypothesized that cancer cells secret functional ST6Gal-I that modulates immune cells’ glycosylation and their activity as a cancer immune evasion mechanism. Also interestingly, patients with PMM2-CDG (the most frequent CDG type) present immunological affectation. Here, we hypothesized that the PMM2-CDG-defective glycosylation observed also influences the function of immune cells. Therefore, the main goals of this study comprised the assessment of the immunological aspects of cancer cells and CDG glycosylation. Specifically, we intended to (1) study the expression and secretion of ST6Gal-I by colorectal cancer (CRC) cells and test its function in modulating immune cells activity; (2) develop a PMM2-CDG leukocyte cell line as a model to unravel patients’ immunity and to evaluate their response to mitogenic stimulation. Moreover, as PMM2-CDG have a profound impact in patients’ quality of life (QoL), patient and observer reported outcomes measures (PROMs and ObsROMs) were reviewed. These may integrate primary endpoints in clinical trials to find treatment to PMM2-CDG. Our data demonstrated that (1) CRC cells secret ST6Gal-I enzyme, however further work is needed to evaluate its role in immune modulation; (2) PMM2-CDG T cells have higher proliferation capacity and IFN-γ cytokine expression, in response to a mitogen as compared to the healthy control and (3) there are significant numbers of tools for future evaluation of PMM2-CDG patients’ and caregivers’ QoL. This study may contribute to better understand the glycan-related pathological mechanisms.